IMPLEMENTASI APLIKASI WEBSITE E-COMMERCE SEBAGAI UPAYA PENINGKATAN PROMOSI PEMASARAN USAHA KECIL DAN MENENGAH - Muttaqin, Rodhotul (Universitas Negeri Semarang, 2017)
Small Business is defined as an economic activity carried out by an individual or a household or an agency aiming to produce goods or services for commercial commission and has a sales turnover of 1 (one) billion rupiah or less. While Medium Business is defined as eco- nomic activity conducted by individual or household as well as an agency aims to produce goods or services for commercial commodity and have sales turnover more than 1 (one) billion. One of the SMEs that developed in Dukuh Delik Wringin Jajar Village Mranggen Dis- trict Demak District is the business of making furniture from aluminum material. This busi- ness has been going on for almost 8 years and able to absorb 5 to 10 workers in the surround- ing environment. Fluctuations in the amount of labor depend heavily on orders demanded by customers. Products produced by SMEs include: Doors, Frames, Window Leaves, Kitch- en Set, Kitchen Cabinets, Storefronts, Corner Display Cabinets, Rolling Door and others. The purpose of community service is to help the SME businessman making furniture from aluminum material in Dukuh Delik Wringin Jajar Village Mr.anggen District De- mak District, especially in the field of marketing. The type of marketing chosen by the dev- otees team is by creating an online store based on Opensource CMS that is Prestashop. The outcome of this program is expected the SMEs business of making furniture from aluminum material has the ability in marketing their products through online store application system that has been made. In addition is expected also with the training and assistance provided by these business actors are able to manage online stores independently. So that will affect the amount of production and orders that will be able to improve the living standards of business actors